Early molecular diagnosis of acute Chagas disease after transplantation with organs from Trypanosoma cruzi-infected donors - Cura, Carolina Inés (2013)
Organ transplantation (TX) is a novel transmission modality of Chagas disease. The results of molecular diagnosis and characterization of Trypanosoma cruzi acute infection in naïve TX recipients transplanted with organs from infected deceased donors are reported. Peripheral blood and cerebrospinal fluid samples from the TX recipients of organs from infected donors were prospectively and sequentially studied for detection of T. cruzi by means of kinetoplastid DNA polymerase chain reaction (kDNA-PCR). In positive blood samples, a PCR algorithm for identification of T. cruzi Discrete Typing Units (DTUs) and quantitative real-time PCR (qPCR) to quantify parasitic loads were performed. Minicircle signatures of T. cruzi infecting populations were also analyzed using restriction fragment length polymorphism (RFLP)-PCR. Eight seronegative TX recipients from four infected donors were studied. In five, the infection was detected at 68.4 days post-TX (36–98 days). In one case, it was transmitted to two of three TX recipients. The comparison of the minicircle signatures revealed nearly identical RFLP-PCR profiles, confirming a common source of infection. The five cases were infected by DTU TcV. This report reveals the relevance of systematic monitoring of TX recipients using PCR strategies in order to provide an early diagnosis allowing timely anti-trypanosomal treatment.